2022
DOI: 10.1590/1807-3107bor-2022.vol36.0092
|View full text |Cite
|
Sign up to set email alerts
|

Are maternal factors predictors of a child’s first dental visit? A birth cohort study in Brazil

Abstract: The purpose of this study was to investigate the association between maternal factors and dental visits of children within their first year of life. This study used data from the 2015 Pelotas Birth Cohort and included pregnant women and their children at 12 months of age, followed-up between May 2014 and December 2015. Socioeconomic and demographic data, information on the use of dental services during the last year, and information on dental fear were collected by interviewing the mothers. Information regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…In keeping with the mean ages at FDV, the percentage of children who had FDV not later than 12 months of age was not much different when compared to Nigeria (0.8%) [ 9 ] and Turkey (2.9%) [ 13 ] and Bulgaria(1.73%) [ 15 ]. Nonetheless, these numbers were far less than the study performed in Brazil (10.1%) which focused only on the infants’ group in urban areas with a ten times larger number of samples [ 16 ]. Furthermore, the oral health status at FDV in our study was comparable to the earlier study in a developed country with good public dental services like Poland: 5.02 ± 4.14 vs. 4.50 ± 3.80 and 1.38 ± 2.12 vs. 0.50 ± 1.00 in primary and permanent dentition, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 93%
“…In keeping with the mean ages at FDV, the percentage of children who had FDV not later than 12 months of age was not much different when compared to Nigeria (0.8%) [ 9 ] and Turkey (2.9%) [ 13 ] and Bulgaria(1.73%) [ 15 ]. Nonetheless, these numbers were far less than the study performed in Brazil (10.1%) which focused only on the infants’ group in urban areas with a ten times larger number of samples [ 16 ]. Furthermore, the oral health status at FDV in our study was comparable to the earlier study in a developed country with good public dental services like Poland: 5.02 ± 4.14 vs. 4.50 ± 3.80 and 1.38 ± 2.12 vs. 0.50 ± 1.00 in primary and permanent dentition, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 93%
“…Noteworthy, Brazil has the largest public health system in the world, which provides preventive and curative care to the entire population, including children, and the system includes strategies for the care of pregnant woman (Smiling Brazil, launched in 2004). The lack of health literacy in relation to the importance of dental visits during the rst years may be a reason for such a low prevalence of dental service use by children [25].…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, Children whose mothers visited the dentist one year before the birth were more likely to have visited the dentist during the first year of life. 31 Shin et al found that the oral health status of children of mothers who had one caries or more were worse than those of mothers who had no caries. 55 It was found that mothers transfer the cariogenic bacteria to their children.…”
Section: The Relationship Between the Carious Status Of The Mothers A...mentioning
confidence: 99%
“…26,[28][29][30] focusing on the social determinants of the parents, 28 their behaviors and practices, 26 and their dental caries status. 31 In Harris et al review, parental oral health behavior was suggested as an important role in determining the oral health of their children. 32 This is why oral health education targeting mothers may positively impact oral the health status of children.…”
Section: Introductionmentioning
confidence: 99%